The promise and pitfalls of fact-checking in 2022 - Amazeen, Michelle (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2024)
Given the evolution and growth of fact-checking around the globe, practitioners and academics have been gathering with increasing frequency to discuss the state of the enterprise. For instance, the first international scientific one-day conference on fact-checking in Athens, Greece assembled in July 2022, to discuss the contribution of universities and research centers in tackling misinformation (EKKE, 2022). Just weeks prior, the 9th annual global fact-checking summit occurred in Oslo, Norway (Larsen, 2022). In October, two conferences convened. Hong Kong Baptist University hosted the virtual conference, ‘Checking the Fact-Checkers: A Global Perspective’ (HKBU, 2022). In the U.S., the 4th annual Conference for Truth and Trust Online gathered in Boston, Massachusetts, providing a forum for academics, industry, non-profit organizations, and other stakeholders to deliberate on the problems facing social media platforms and technical solutions –including fact-checking– to understand and address them (Truth, n.d.). Thus, the continued interest in fact-checking suggests periodic updates on how the practice is evolving has merit.The present article is one such effort which briefly addresses the origins of fact-checking followed by an examination of some of the challenges and opportunities facing the enterprise.